Old-house dictionary : an illustrated guide to American domestic architecture, 1600-1940 - Phillips, Steven J. (American Source Books, 1989)
Old-House Dictionary From a One Room Cabin to a Beaux-Arts Mansion. Here's a concise and easily understandable architectural dictionary for professionals and amateurs alike. More than 450 illustrations, 1500 terms, 750 definitions, and 17 useful cross references guide you smoothly through the oftentimes confusing language of American domestic architecture.--Amazon.